2007
DOI: 10.4161/epi.2.3.4841
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Mecp2 Expression During a Critical Period of Rat Brain Development

Abstract: Pervasive developmental disorder is a classification covering five related conditions including the neurodevelopmental disorder Rett syndrome (RTT) and autism. Of these five conditions, only RTT has a known genetic cause with mutations in Methyl-CpG-binding protein 2 (MeCP2), a global repressor of gene expression, responsible for the majority of RTT cases. However, recent evidence indicates that reduced MeCP2 expression or activity is also found in autism and other disorders with overlapping phenotypes. Consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 27 publications
4
69
1
Order By: Relevance
“…Females expressed higher levels of this X-chromosome gene associated with the neurodevelopmental disorder, Rett Syndrome, than did males. Others have reported a similar sex difference in Mecp2 expression in the postnatal day one rat amygdala (77), which indirectly supports our result by suggesting that the sex difference is organized by early estradiol exposure. The same group also showed that sexually dimorphic Mecp2 expression in the amygdala is required for the development of sexually dimorphic behaviors in later life (78).…”
Section: Discussionsupporting
confidence: 91%
“…Females expressed higher levels of this X-chromosome gene associated with the neurodevelopmental disorder, Rett Syndrome, than did males. Others have reported a similar sex difference in Mecp2 expression in the postnatal day one rat amygdala (77), which indirectly supports our result by suggesting that the sex difference is organized by early estradiol exposure. The same group also showed that sexually dimorphic Mecp2 expression in the amygdala is required for the development of sexually dimorphic behaviors in later life (78).…”
Section: Discussionsupporting
confidence: 91%
“…In this light, mutations in regulatory regions may be tolerable to the brain of the developing male but induce phenotypic variations. Studies in rat brain have shown significantly less Mecp2 mRNA and protein expression in the amygdala of male rat brain during the steroidsensitive period of brain development (35). Ultimately, there is ample evidence suggesting that regulation of MECP2 is different between genders, consistent with our observations of the differential influence of MECP2 variations on brain structure in males and females.…”
Section: Discussionsupporting
confidence: 88%
“…Although the first studies on specific epigenetic mechanisms in brain sexual differentiation appeared less than 10 years ago [7][8][9][10], circumstantial evidence that epigenetics plays a role was available much earlier. For example, most known sex differences in the brain depend on gonadal steroid hormones, acting during a critical developmental window [11].…”
Section: Sexual Differentiation and Epigeneticsmentioning
confidence: 99%